2022
DOI: 10.1080/21655979.2022.2036891
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-631 deriving from bone marrow mesenchymal stem cell exosomes facilitates the malignant behavior of non-small cell lung cancer via modulating the E2F family of transcription factor 2/phosphatidylinositol 3‐kinase/Akt signaling pathway

Abstract: The exosomes (Exo) had always been considered as transport vectors for microRNA (miRNA). An increasing number of data had clarified the influence of Exo on the cell progression of non-small cell lung cancer (NSCLC). Nevertheless, its specific mechanism had not yet been verified. This work was to explore the potential mechanism of Exo-derived miR-631 targeting and regulating E2F family of transcription factor 2 (E2F2) to repress the malignant behavior of NSCLC cells. Test of microRNA (miR)-631 and E2F2 in NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Engineered MSC-exos can serve as effective biological carriers that exert regulatory effects on the malignant behaviours of lung cancer cells, including proliferation, migration, invasion, and metastasis. Studies have shown that in NSCLC cell models and animal models, engineered MSC-derived exo-mediated miR-631 delivery could control NSCLC malignant behaviours by regulating the transcription factor 2/phosphatidylinositol 3-kinase/Akt signalling pathway [ 72 ]. Engineered MSC-exos transport and deliver miR-204 to act on NSCLC cells, and the overexpression of miR-204 inhibits KLF7 expression and AKT/HIF-1α pathway activity, thereby inhibiting NSCLC migration and invasion [ 73 ].…”
Section: Chronic Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineered MSC-exos can serve as effective biological carriers that exert regulatory effects on the malignant behaviours of lung cancer cells, including proliferation, migration, invasion, and metastasis. Studies have shown that in NSCLC cell models and animal models, engineered MSC-derived exo-mediated miR-631 delivery could control NSCLC malignant behaviours by regulating the transcription factor 2/phosphatidylinositol 3-kinase/Akt signalling pathway [ 72 ]. Engineered MSC-exos transport and deliver miR-204 to act on NSCLC cells, and the overexpression of miR-204 inhibits KLF7 expression and AKT/HIF-1α pathway activity, thereby inhibiting NSCLC migration and invasion [ 73 ].…”
Section: Chronic Lung Diseasesmentioning
confidence: 99%
“…Studies have shown that human bone marrow-derived MSC-exos (BMSC-exos) can deliver miR-425 into lung cancer cells, inhibit CPEB1 expression, and promote lung cancer cell proliferation, invasion, and metastasis [ 75 ]. Furthermore, studies have shown that human BMSC-exos can mediate E2F2 expression by delivering miR-631 to NSCLC cells to regulate NSCLC malignant behaviours [ 76 ]. Considering the relationship between malignant lung cancer behaviours and their internal death outcomes, engineered MSCs may be a treatment that promotes programmed death in tumour cells, but their safety and effectiveness still need to be considered.…”
Section: Chronic Lung Diseasesmentioning
confidence: 99%
“…E2F2 is a normative transcription factor, which joins in transcription regulation, cell cycle, and tumorigenesis 18 . Several researches uncovered that miRNAs modulated NSCLC cell proliferation and invasion via targeting E2F2 19,20 . But, whether miR‐637 joins in regulating the function of circ_0000877 through targeting E2F2 in NSCLC cells remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…18 Several researches uncovered that miRNAs modulated NSCLC cell proliferation and invasion via targeting E2F2. 19,20 But, whether miR-637 joins in regulating the function of circ_0000877 through targeting E2F2 in NSCLC cells remains unexplored.…”
mentioning
confidence: 99%
“…Increasing studies have suggested the inhibiting property of bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exos) in the development of various tumors [ 5 , 6 ]. BMSC-Exos can restrain the growth and progression of breast cancer cells in vitro and in vivo [ 7 ].…”
Section: Introductionmentioning
confidence: 99%